A special solar collector for ammonia-water absorption refrigeration - Tsai, Sing-Tsu; Exell, Robert H.B.; Saunier, G.Y.; Walter, Despiegelaere, Ir.; Bhattacharya, Sribas C.; RSEA, ROC (Bangkok : Asian Institute of Technology, 1981)
A new design for the generator-absorber in the form of a flat-plate solar collector having 13 mm risers thermally attached to a black plate 2 m long by 0.3 m wide and two 50 mm return tubes acting as a solution reservoirs has been constructed and tested. Fast heating and distillation of ammonia occurs due to the low heat capacity of the plate, while rapid cooling of t he generator and reabsorption of ammonia during -refrigeration at night is obtained by removing the back insulation. Using 10.1 kg of aqua-ammonia with ammonia concentration 46% by weight, l. 5 kg of ammonia could be distilled on a typical day, and 3 kg could be distilled with the helps of booster mirrors in the collector. This yield is a considerable improvement on yields from previous designs in AIT. Estimates of the thermosyphon velocity show that in bright sunlight, the solution in the collector circulates once per minute.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Environment, Resources and Development
Thesis (M.Eng.) - Asian Institute of Technology, 1981
Keywords: Solar energy research; Refrigerators